Europe: A space special area of human hope (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2016)
This article tackles the issue of the protection of Human Rights in the European Union. The Constitutional Treaty incorporates at its Part II the European Union Charta onFundamental Rights. Moreover, the Constitutional Treaty contemplates the adhesion of the EU to the European Convention on Human Rights. These two novelties would change the scenario of human rights protection in Europe.Perhaps the most controversial question to be solved is which would be the European Court to settle final case-Law on human rights. Would it be the Court of Luxemburg? What about relationship between Luxemburg Court and Strasbourg Court? And the relationship between national Constitutional Courts and the Court of Justice of the UE? Whatever the answer, in any case International Law on Human Rights states that the most guarantist interpretation of the fundamental human rights normative must prevail.
Keywords: Fundamental human rights. International Law on Human Rights. Constitutional Treaty. European Union Chartre of Fundamental Rights. Court of Justice of the European Union. European Convention on Human Rights. European Court on Human Rights.